The insoluble problems of crime - Rhodes, Robert P. (Wiley, 1977)
The political conflicts inherent to the criminal justice system are analyzed and the practical policy solutions that can reduce criminal behavior while preserving criminal justice are discussed. The analysis provides a conceptual framework for measuring success or failure in criminal justice policy. It is dialectic in style, recognizing that the criminal justice system has competing objectives - civil liberty protection, effective apprehension, order maintenance, deterrence - and that a democratic public policy must contain multiple goals even though they are often competing with one another. Some of the policy issues discussed include drug control, court delay, bail bond reform, gun control, and plea bargaining. While there is no bibliography, the text is heavily footnoted and the references are indexed by author. A subject index to the book is also provided. Graphs and tabular data are included.